Capacitive performance of amino acid ionic liquid electrolyte-based supercapacitors by molecular dynamics simulation. Issue 46 (1st June 2017) - Wu, Mingbing; Li, Wei; Li, Song; Feng, Guang
Abstract : Capacitance–electric potential curves of amino acid ionic liquid electrolyte-based supercapacitors. Abstract : The performance of amino acid ionic liquid (AAIL) electrolytes in electrical double layers (EDLs) near planar graphene electrodes was investigated by classical molecular dynamics (MD) simulations in this work. Four types of AAILs, 1-ethyl-3-methylimidazolium glycine ([EMIM][GLY]), 1-ethyl-3-methylimidazolium serine ([EMIM][SER]), 1-ethyl-3-methylimidazolium valine ([EMIM][VAL]) and 1-ethyl-3-methylimidazolium phenylalanine ([EMIM][PHE]), with different amino acid anions were selected as electrolytes for supercapacitors. The number density profiles and ion orientation at varying surface charge densities were delineated to exploit the microstructure of EDLs for different AAILs. As a result, similar EDL structures of cations near a negative graphene electrode were observed, whereas the EDLs at positively charged electrodes displayed dependence on amino acid anions. AAILs composed of the common cation [EMIM] + and dissimilar amino acid anions exhibit similar differential capacitance–electrical potential ( C – V ) curves and comparable capacitance to conventional ionic liquids.